Effect of different carbon materials as electron shuttles in the anaerobic biotransformation of nitroanilines - Pereira, Luciana (2016)
Aromatic amines resulted from azo dyes biotransformation under anaerobic conditions are generally recalcitrant to further anaerobic degradation. The catalytic effect of carbon materials (CM) on the reduction of azo dyes is known and has been confirmed in this work by increasing 3-fold the biological reduction rate of Mordant Yellow 1 (MY1). The resulting m-nitroaniline (m-NoA) was further degraded to m-phenylenediamine (m-Phe) only in the presence of CM. The use of CM to degraded anaerobically aromatic amines resulted from azo dye reduction was never reported before. In the sequence, we studied the effect of different CM on the bioreduction of o-, m- and p-NoA. Three microporous activated carbons with different surface chemistry, original (AC0), chemical oxidized with HNO3 (ACHNO3) and thermal treated (ACH2), and three mesoporous carbons, xerogels (CXA and CXB) and nanotubes (CNT) were assessed. In the absence of CM, NoA were only partially reduced to the corresponding Phe, whereas in the presence of CM, more than 90% was converted to the corresponding Phe. ACH2 and AC0 were the best electron shuttles, increasing the rates up to 8-fold. In 24h, the biological treatment of NoA and MY1 with AC0, decreased up to 88% the toxicity towards a methanogenic consortium, as compared to the non-treated solutions. This article is protected by copyright. All rights reserved